The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1111/age.13062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a large dataset of SNPs in hair‐fin anchovy (Setipinna tenuifilis) based on RAD‐seq

Abstract: Hair-fin anchovy (Setipinna tenuifilis) is an economically important fish distributed in the West Indian Ocean and the Northwest Pacific Ocean. In this study, 154 individuals in eight populations of S. tenuifilis were sequenced and 850 million raw reads were obtained using restriction site-associated DNA sequencing (RAD-seq). First, we identified 14 012 044 hypothetical SNP markers. A dataset of 199 903 high-quality SNPs was collected after further screening. These SNPs have a strong ability to test the geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In Figure 1c, the QD and ZS populations were grouped into one cluster and the ZJ population was independently grouped into another cluster, which was consistent with previous studies, showing a discontinuity between northern and southern populations (Peng et al, 2021). Our results showed that the newly polymorphic SSR markers developed in this study could assess the different population structures of this species across its distribution range.…”
Section: Re Sults and Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In Figure 1c, the QD and ZS populations were grouped into one cluster and the ZJ population was independently grouped into another cluster, which was consistent with previous studies, showing a discontinuity between northern and southern populations (Peng et al, 2021). Our results showed that the newly polymorphic SSR markers developed in this study could assess the different population structures of this species across its distribution range.…”
Section: Re Sults and Discussionsupporting
confidence: 90%
“…Mitochondrial DNA (mtDNA) sequences and single nucleotide polymorphisms (SNPs) have been used in population genetic studies of S. tenuifilis (Peng et al, 2021; Xu et al, 2014). Maternal inheritance and absence of recombination make mtDNA an important role as a genetic marker in population and evolutionary biology (Harrison, 1989), but it is limited to uncovering the fine population structure of marine fish compared to nuclear genes (Hellberg et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Simple library construction, short duration of the experiment, and well-developed data processing and analysis pipelines have made the RAD-seq technology popular in SNP identification and population genetics studies (Eaton and Ree 2013 ; McCormack et al 2013 ). Furthermore, RAD-seq technology has been successfully applied to detect SNPs in the whole genome of numerous marine species, such as Mugil cephalus (Krück et al 2013 ), Carcinus maenas (Jeffery et al 2017 ) and Setipinna tenuifilis (Peng et al 2021 ), to provide more reliable evidence for studying their genetic structure and adaptive evolution (Miller et al 2007 ). However, no population genetics study has been conducted to detect genome-wide SNPs of K. punctatus based on RAD-seq.…”
Section: Introductionmentioning
confidence: 99%